PANTANG LARANG ADAT BERSALIN MASYARAKAT MELAYU PADA TAHUN 1992 – 2011 (Studi Kasus Desa Pesisir Timur Kecamatan Siantan Kabupaten Kepulauan Anambas) - Lisawati '; Isjoni '; Kamaruddin Oemar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak:Thepurpose of this research is (1) to know the level of implementation of the abstinence forbids the maternity malay community in the country’s eastern coast during pregnacy (2) to know the level of incurred in implementation the abstinence forbids the maternity in the eastern coast village at the time of birth (3) to know the level of incurred in implementation the abstinence forbids the maternity in the eastern coast village in the post partum period (4) to know defermine the value conpained behind the eastern coast villiage (5) to know is wheter the malay community in the eastren coast villiages that hold fas to traditional childbirth from year 1992-2011. In this research method qualitative where this matter will give the comlete information so that be of benefit to science. Resulth from this research that the rural communities in the eastren costal distrik Siantan Anambas island in 1992-2011. Although there most certainly no longer wear midwife. In general many people go to the hospital. But, retained the traditional abstinence and held in this case the level of the abstinence forbids the maternity community must continue to be maintained. Aside from being a cultural preservation efforts. A dherence to local costoms is also a rescue effort for mother and baby.Key words : Abstinense Forbids The Maternity Malay Community